Coutume Autochtone et Evolution du droit dans le Pacificque Sud - Angelo, A H (Victoria University of Wellington Law Review, 1996)
This article is a book review of Paul de Deckker Coutume Autochtone et Evolution du droit dans le Pacficique Sud (1st ed, L'Harmattan, Paris, 1995) 304pp. The book is the product of a colloquium on indigenous custom and the development of law in the South Pacific, held in New Caledonia in July 1994. The papers from the colloquium provide a commentary and resource book on customary law in the South Pacific, with particular reference to the French territories of French Polynesia, New Caledonia, and Wallis and Futuna. Angelo argues that the book is good for reading, as an educational resource, and as stimulus to thought on the complex issues of the day. It is concluded that the book is an important contribution to the literature on the subject of law and custom, and presents in an accessible French much data not available elsewhere.